Community-Based Halal Tourism Village: Insight from Setanggor Village - Adinugraha, Hendri Hermawan; Nasarruddin, Razie Bin; Rofiq, Ahmad; Ulamaâ€™i, Ahmad Hasan Asyâ€™ari; Mujaddid, Ade Yusuf; Sartika, Mila (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2020)
Abstract:Â This research aims to describe the development model of Setanggor halal tourism village. This research uses qualitative research methods with a descriptive approach. The results showed that halal tourism in Setanggor village was developed through active community participation with the village government through a tourism village model based on community and halal values. The development of halal tourism villages in Setanggor is not able to be separated from religious values. As a result, Community-Based Halal Tourism in Setanggor village combines community-based tourism and halal-based tourism that will eventually serve as a model for community-based halal tourism. The growth of the halal tourism sector in Setanggor village has also provided positive benefits for enhancing the local community's well-being. In addition to the community's active role, the legality of the Setanggor halal tourism village is also supported by the local government of NTB and the Indonesian Council of Ulama.Abstrak:Â Penelitian ini bertujuan untuk mendeskripsikan model pengembangan desa wisata halal Setanggor. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan deskriptif. Hasil penelitian menunjukkan bahwa wisata halal di Desa Setanggor dikembangkan melalui partisipasi aktif masyarakat dengan pemerintah desa melalui model â€œDesa Wisata Halal Berbasis Masyarakatâ€. Pengembangan desa wisata halal di Setanggor tidak lepas dari nilai-nilai religi. Oleh karena itu, CBT di desa Setanggor yang merupakan gabungan antara pariwisata berbasis komunitas dengan pariwisata berbasis halal pada akhirnya menjadi role model bagi wisata halal berbasis komunitas. Pertumbuhan sektor wisata halal di desa Setanggor juga memberikan manfaat positif bagi peningkatan kesejahteraan masyarakat setempat. Selain peran aktif masyarakat, legalitas desa wisata halal Setanggor juga didukung oleh pemerintah daerah NTB dan Majelis Ulama Indonesia.